2015
DOI: 10.4103/0301-4738.154400
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy in mild to moderate keratoconus: Outcomes in over 40-year-old patients

Abstract: Background:Keratoconus is a contraindication for photorefractive keratectomy (PRK). In the recent decade, some efforts have been made to perform PRK in patients with keratoconus whose corneas are stable naturally or by doing corneal collagen crosslinking. These studies have suggested residual central corneal thickness (CCT) ≥450 μm.Aims:The aim was to evaluate the long-term outcomes of PRK in patients with mild to moderate keratoconus in patients older than 40 with residual CCT ≥ 400 μm.Settings and Design:Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Among the remaining 19 eyes, corrected distance visual acuity was improved in 16 (84.3%), declined in two (10.5%), and unchanged in one (5.2%) eyes. Also Khakshoor et al reported similar results in patients older than 40 years with grade I or II keratoconus ( 19 ). In the mentioned study, variables such as keratometric readings, uncorrected visual acuity, best corrected visual acuity, spherical equivalent, and cylindrical power were evaluated.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among the remaining 19 eyes, corrected distance visual acuity was improved in 16 (84.3%), declined in two (10.5%), and unchanged in one (5.2%) eyes. Also Khakshoor et al reported similar results in patients older than 40 years with grade I or II keratoconus ( 19 ). In the mentioned study, variables such as keratometric readings, uncorrected visual acuity, best corrected visual acuity, spherical equivalent, and cylindrical power were evaluated.…”
Section: Discussionmentioning
confidence: 64%
“…Our findings are compatible with similar studies. Some studies on the efficacy and safety of PRK in keratoconus have reported a low risk for progression of keratoconus ( 6 , 19 ). Atypical indices, including inferior steepening, high keratometery, low pachymetery, high anterior and posterior elevation and high SRAX had no influence on the rate of keratoconus in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies concluded that PRK in eyes with suspected keratoconus, carefully selected, might be a safe and effective procedure for reducing or eliminating myopia and/or astigmatism. Two studies evaluated the PRK in patients with mild to moderate stable keratoconus [ 20 , 21 ]. Chelala et al [ 20 ] in a five-year follow-up study analysed the visual outcomes of PRK in 119 eyes with grade 1-2 keratoconus according to Amsler-Krumeich classification.…”
Section: No Combined Proceduresmentioning
confidence: 99%
“…Only two eyes (1.7%) showed progression of the disease at 5 years of follow-up. In the Khakshoor et al [ 21 ] study, 38 stable keratoconus (grades I-II, Amsler-Krumeich) of 21 patients over 40 years old were recruited. At the last follow-up visit, in 22 eyes, the UDVA was 20/20 and in 8 eyes 20/25.…”
Section: No Combined Proceduresmentioning
confidence: 99%
See 1 more Smart Citation